The small eye phenotype in the EPIC-Norfolk eye study: prevalence and visual impairment in microphthalmos and nanophthalmos. Issue 7 (24th July 2013) - Day, Alexander C; Khawaja, Anthony P; Peto, Tunde; Hayat, Shabina; Luben, Robert; Broadway, David C; Khaw, Kay-Tee; Foster, Paul J
Abstract : Objective: To describe the prevalence and phenotypic characteristics of small eyes in the European Prospective Investigation of Cancer (EPIC)-Norfolk Eye Study. Design: Community cross-sectional study. Setting: East England population (Norwich, Norfolk and surrounding area). Participants: 8033 participants aged 48–92 years old from the EPIC-Norfolk Eye Study, Norfolk, UK with axial length measurements. Participants underwent a standardised ocular examination including visual acuity (LogMAR), ocular biometry, non-contact tonometry, autorefraction and fundal photography. A small eye phenotype was defined as a participant with one or both eyes with axial length of <21 mm. Outcome measures: Prevalence of small eyes, proportion with visual impairment, demographic and biometric factors. Results: Ninety-six participants (1.20%, 95% CI 0.98% to 1.46%) had an eye with axial length less than 21 mm, of which 74 (77%) were women. Prevalence values for shorter axial lengths were <20 mm: 0.27% (0.18% to 0.41%); <19 mm: 0.17% (0.11% to 0.29%); <18 mm: 0.14% (0.08% to 0.25%). Two participants (2.1%) had low vision (presenting visual acuity >0.48 LogMAR) and one participant was blind (>1.3 LogMAR). The prevalence of unilateral visual impairment was higher in participants with a small eye. Multiple logistic regression modelling showed presence of a small eye to be significantly associated with shorter height, lower body mass index, higher systolic blood pressure and lower intraocular pressure. Conclusions: The prevalence of people with small eyes is higher than previously thought. While small eyes were more common in women, this appears to be related to shorter height and lower body mass index. Participants with small eyes were more likely to be blind or to have unilateral visual impairment.